Von ’inspirierenden Orten’ und ’Safe Places’. Die ästhetische Nutzung von Orten in der Appmusikpraxis - Eusterbrock, Linus; Godau, Marc; Haenisch, Matthias; Krebs, Matthias; Rolle, Christian (Musikpädagogik im Spannungsfeld von Reflexion und Intervention)
Although music apps are becoming increasingly popular, there has been little research on informal music practices with apps. This article presents findings of an ongoing study on learning processes and aesthetic experiences with informal appmusic practices. In particular, it discusses the aesthetic practices (Reckwitz, 2008b) of using specific places for making music. In our grounded theory study (Charmaz, 2014) we collected data using interviews, participant observation and videography. As exemplary cases, this article presents two analyses of the use of ‘inspiring places’ and ‘safe places’. The results suggest that perceiving the atmosphere is a fundamental prerequisite for both places. Additionally, the results shed light on aesthetic aspects of mobile music making. (DIPF/Orig.)
Keywords: Education; Ästhetik; Schul- und Bildungswesen; Informal learning; Informelles Lernen; Musical education; Musikpädagogik; Anwendung; Ästhetische Erfahrung; Grounded Theory; Längsschnittuntersuchung; Learning process; Lernprozess; Longitudinal analysis; Longitudinal study; Mobiles Gerät; Music reading; Musizieren; Erziehung